Evaluation of access policies and practices of selected academic archive services in Metro Manila - Varona, Ronie Von L. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
This study evaluated the access policies and practices of seven selected academic archive services in Metro Manila based on the perceived compliance to the standard of the heads of each academic archive service.